Examining the Interconnections Among Tourism, Energy Consumption, Environmental Pollution, and Economic Growth in the Fragile Five Countries: A Panel Quantile Regression Analysis - Ramashova, Aissulu Nurmambekovna; Alshanov, Rakhman A.; Zhunusbekova, Nazym; Abishova, Aizhan Urinbasarovna; Sartanova, Nalima; Baisholanova, Karlygash Sovetovna; Dauzova, Aida Mazhidovna; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2025)
This study examines how the relationship between economic growth and tourism revenues, energy intensity, and CO2 emissions in the Fragile Five countries (Brazil, Indonesia, India, South Africa, and Turkey) varies across different growth regimes using Panel Quantile Regression. The analysis utilizes data from 1995 to 2023, which includes metrics such as GDP growth rate, the share of international tourism revenues in exports, energy intensity (measured in kg of oil equivalent/$1,000 of GDP with a constant 2021 PPP), and CO2 emissions, all retrieved from the World Bank. Cross-sectional dependence was assessed using the Breusch-Pagan LM test, while stationarity was evaluated with the second-generation CIPS test, and appropriate level or difference transformations were applied. The findings indicate that tourism revenues have a positive and statistically significant effect on growth in the lower quantile (25%), with a borderline significant positive effect observed in the median quantile (50%). Energy intensity negatively and significantly impacts growth in both the lower (25%) and upper (75%) quantiles, highlighting that productivity constraints are obvious in both low- and high-growth regimes. Additionally, CO2 emissions exhibit a positive and significant relationship with growth in the upper (75%) quantile, suggesting that increases in emissions are associated with economic booms during periods of rapid expansion. Overall, by emphasizing distribution- sensitive heterogeneities that linear approaches based on average effects may overlook, this study underscores the need for quantile-specific policy designs. These policies should aim to support tourism demand and employment in low-growth regimes while focusing on energy efficiency and cleaner production technologies in high-growth contexts. The conclusion is that tourism contributes to growth in certain regimes; energy intensity remains a persistent constraint; and managing the relationship between emissions and growth is crucial for sustainability during high-growth phases.